An Irreversible Method-Opinions of Women with Tubal Ligation in Turkey: A Qualitative Study - Fatma Şule Bilgiç; Aysu Yıldız Karaahmet (JOURNAL OF BIOTECHNOLOGY AND STRATEGIC HEALTH RESEARCH, 2026)
Background: It is stated that for women who do not want to have more children, tubal ligation may be a good choice. Among the techniques used to prevent pregnancy, the most focused is on the process of cutting-connecting the tubes.Objective: This study was conducted to examine the opinions of women who use tubal ligation as a family planning method.Methods: The qualitative study desing. The 11 women using tubal ligation as a family planning method, consisted of the study. The qualitative study conducted between January and February 2023. The opinions of women using tubal ligation about the method were collected by individual in-depth interview method using a semi-structured interview form. The data obtained from the interview were analyzed through content analysis.Results: This qualitative study is based on data from 11 interviews about tubal ligation used by women living in Turkey. In the article, decision making process, the effect of family planning on sexual life and belief 3 main themes were determined. It was determined that women do not want to have children again and that it is a definite method in deciding tubal ligation. It was determined that the women were very comfortable in the tubal ligation method and provided comfort. It was determined that when women preferred tubal ligation, there were many negative environmental reactions and it contradicted their beliefs.Conclusion: In order for family planning (FP) research and interventions to be successful in achieving equitable and rights-based access to FP, they must adopt a community- and women-centred approach, collaboratively exploring the norms, religion, and lifestyle factors surrounding FP.